Elevated cardiac enzymes due to mushroom poisoning - Avcı, Sema; Usul, Eren; Kavak, Nezih; Büyükcam, Fatih; Arslan, Engin Deniz; Genç, Selim; Özkan, Seda (Acta Biomedica Atenei Parmensis, 2014)
Mushroom poisoning is an important reason of plant toxicity. Wild mushrooms that gathered from pastures and forests can be dangerous for human health. The clinical outcomes and symptoms of mushroom toxicity vary from mild gastrointestinal symptoms to acute multiple organ failure. Toxic effects to kidney and liver of amatoxin are common but cardiotoxic effects are unusual. In this case, we reported the cardiotoxic effect of amatoxin with the elevated troponin-I without any additional finding in electrocardiography, echocardiography and angiography